THE LOAN CONTRACT IN THE NEW CIVIL CODE - LIVIA MOCANU (Challenges of the Knowledge Society, 2012)
The new Civil Code maintains, mainly, the stipulations of the Civil Code of 1865 regarding loan contracts, in its both forms (the loan for use and the loan for consumption). As a variety of the loan for consumption, a few new specific stipulations were included, regarding the loan with interest.This research is focused on the current regulation of the loan contract, including a series of changes, of which the most important refers to: the loan promise, the risk regarding the asset placed in a bailment, property transfer and the risk in the loan for consumption contract, loan return and the interest regime. Also, what kept my attention is the significant changes brought to the interest regime by the Law for applying the Civil Code, included for now in Chapter I of the O.G. no. 13/2011, regarding the legal compensatory interest and the penalty interest for financial duties, as well as for the regulation of certain financial-fiscal measures in the banking department.